2018
DOI: 10.1093/jnci/djy150
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Susceptibility Loci for Radiation-Induced Brain Injury

Abstract: Background Radiation-induced brain injury is a nonnegligible issue in the management of cancer patients treated by partial or whole brain irradiation. In particular, temporal lobe injury (TLI), a deleterious late complication in nasopharyngeal carcinoma, greatly affects the long-term life quality of these patients. Although genome-wide association studies (GWASs) have successfully identified single nucleotide polymorphisms (SNPs) associated with radiation toxicity, genetic variants contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 53 publications
1
31
0
1
Order By: Relevance
“…Cerebrovascular injury and remodeling is an underlying hypothesis for the development of RTLI. Recently, a genome-wide association study implicated the genetic susceptibility gene CEP128 in RTLI development [31]. Generally, the particular mechanism of RTLI includes not only demyelination, softening, and necrosis of white matter, but also nerve and glial cell damage caused by direct radiation, which are related to gray matter [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular injury and remodeling is an underlying hypothesis for the development of RTLI. Recently, a genome-wide association study implicated the genetic susceptibility gene CEP128 in RTLI development [31]. Generally, the particular mechanism of RTLI includes not only demyelination, softening, and necrosis of white matter, but also nerve and glial cell damage caused by direct radiation, which are related to gray matter [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although CRN in uenced by various risk factors such as total radiation dose, dose per fraction, treatment duration, irradiated volume, and concurrent use of chemotherapy, the rapidly progressive course of CRN raises the susceptibility of underlying genetic mechanisms (4-7). A prospective cohort study by Wang TM et al in 2019, implicated a radiation injury susceptibility gene (Cep128) as an underlying mechanism of radiationinduced brain injury, as it tightly interacts with multiple radiation-resistant genes (7).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that immediate, adjuvant RT appears to be strongly associated with improved survival rate of high-grade meningiomas (2,3). CRN is the most relevant side effect after RT and can masquerade as tumor recurrence (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Thus, both establishing an accurate diagnosis and reaching a prompt treatment decisions are challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic susceptibility studies for radiation-induced central nervous system toxicity are starting to emerge. Wang et al [ 42 ] conducted a three-stage GWAS study with more than 1,000 patients for each stage. Their analysis identified SNPs near the gene CEP128 , which codes a centrosome protein involved in cell cycle progression, and is associated with temporal lobe injury risk (HR=1.45; 95% CI, 1.26–1.66).…”
Section: Head and Neck Irradiationmentioning
confidence: 99%